Size-selective synthesis of platinum nanoparticles on transition-metal dichalcogenides for the hydrogen evolution reaction. Issue 23 (22nd February 2021) - Mei, Liang; Gao, Xiaoping; Gao, Zhan; Zhang, Qingyong; Yu, Xinge; Rogach, Andrey L.; Zeng, Zhiyuan
Abstract : Pt-MoS2 composites are fabricated via growing tunable Pt nanoparticles size (NPs, 2–6 nm) on single-layer MoS2 nanosheets. Which have shown excellent performance for hydrogen evolution reaction (HER) with the Pt NPs exhibiting a volcano-type size effect toward mass activity due to the synergistic effects between the Pt NPs and MoS2. Abstract : We report a micellar system to prepare Pt-TMDs composites with tunable Pt nanoparticles (NPs, 2–6 nm in size) on single-layer TMDs (MoS2, TiS2, TaS2 ) nanosheets. The Pt–MoS2 composites have shown excellent performance for the hydrogen evolution reaction (HER) with the Pt NPs exhibiting a volcano-type size effect toward HER activity due to the synergistic effects between the Pt NPs and MoS2 .